Fludarabine‐based reduced toxicity yet myeloablative conditioning is effective and safe particularly in patients with high‐risk thalassemia undergoing allogeneic transplantation. Issue 11 (1st August 2018) - Sheth, Vipul; Grisariu, Sigal; Avni, Batia; Stepensky, Polina; Ashkenazi, Maayan; Shapira, Michael Y.; Or, Reuven
Abstract: Introduction: Thalassemia major (TM) is an inherited disorder caused by ineffective erythropoiesis. At the present time, allogeneic stem cell transplantation (allo‐SCT) is a curative option. Conventional busulfan and cyclophosphamide based myeloablative conditioning regimens are limited by increased toxicity, especially in high‐risk patients. Replacement of cyclophosphamide with fludarabine has reduced toxicity and nonrelapse mortality (NRM), thus improving outcomes. We analyzed long‐term data of our fludarabine‐based myeloablative, reduced toxicity protocol, specifically in high‐risk patients. Methods: We retrospectively analyzed a cohort of 47 consecutive patients with TM undergoing allo‐SCT from matched donors, using the fludarabine‐based regimen (reduced toxicity regimen). The median age of the cohort was 10 years. Thirty‐eight patients (80%) were in the high‐risk and nine patients (20%) were in the low‐risk category. The primary aim of this analysis was thalassemia‐free survival (TFS). Results: The rejection rate was 11% within high‐risk patients with NRM of 2%. With a median follow‐up period of 7 years (1–15 years), the 10‐year TFS in the entire cohort was 87%, and the overall survival (OS) was 97%. The 10‐year TFS and OS among the low‐risk and high‐risk groups were 90% versus 84%, respectively ( P = 0.45) and 100% versus 96%, respectively ( P = 0.5), and both subsets of patients did equally well. Conclusion: In conclusion, replacement of high‐dose cyclophosphamide with fludarabine is well tolerated with minimal regimen‐related toxicity and acceptable rejection rates, especially in high‐risk patients.